Charged Particles in Oncology - Marco Durante (Frontiers Research Topics, 2018)
High-energy charged particles represent a cutting-edge technique in radiation oncology. Protons and carbon ions are used in several centers all over the world for the treatment of different solid tumors. Typical indications are ocular malignancies, tumors of the base of the skull, hepatocellular carcinomas and various sarcomas. The physical characteristics of the charged particles (Bragg peak) allow sparing of much more normal tissues than it is possible using conventional X-rays, and for this reason all pediatric tumors are considered eligible for protontherapy. Ions heavier than protons also display special radiobiological characteristics, which make them effective against radioresistant and hypoxic tumors. On the other hand, protons and ions with high charge (Z) and energy (HZE particles) represent a major risk for human space exploration. The main late effect of radiation exposure is cancer induction, and at the moment the dose limits for astronauts are based on cancer mortality risk. The Mars Science Laboratory (MSL) measured the dose on the route to Mars and on the planet's surface, suggesting that a human exploration missions will exceed the radiation risk limits. Notwithstanding many studies on carcinogenesis induced by protons and heavy ions, the risk uncertainty remains very high. In this research topic we aim at gathering the experiences and opinions of scientists dealing with high-energy charged particles either for cancer treatment or for space radiation protection. Clinical results with protons and heavy ions, as well as research in medical physics and pre-clinical radiobiology are reported. In addition, ground-based and spaceflight studies on the effects of space radiation are included in this book. Particularly relevant for space studies are the clinical results on normal tissue complications and second cancers. The eBook nicely demonstrates that particle therapy in oncology and protection of astronauts from space radiation share many common topics, and can learn from each other.